Effective Strategies for Second Language Acquisition: The Role of Educational Management in Improving Learning Quality - Ismunadar, Arif; Muntoha, Tohir; Wulandari, Citra Eka (CV. Goresan Pena, 2023)
Second language learning faces significant challenges, such as low student motivation, limited resources, and a lack of teacher training, which can hinder learning effectiveness. Ineffective educational management in curriculum and language policy implementation may exacerbate these conditions, making exploring effective strategies for supporting second language acquisition essential. This study aims to identify and analyze effective educational management strategies in supporting second language acquisition and solutions to challenges encountered in their implementation. Additionally, this research seeks to provide recommendations on policies and teaching approaches to enhance the quality of second language learning. The research method used is a literature review involving collecting and analyzing relevant articles and scientific journals. This study explores various literature on educational management, second language teaching strategies, and technology in language learning. The findings indicate that effective educational management—such as curriculum development based on authentic communication, the use of technology in learning, and teacher training—can improve the effectiveness of second language acquisition. The main challenges include low student motivation and limited resource access, which can be addressed through technology-based approaches and more inclusive policies.